Small scale contractional-extensional structures and morphotectonics along the fault traces of Izmit-Cocaeli (Turkey) 1999 earthquake - TUTKUN, Z.; PAVLIDES, S. (Bulletin of the Geological Society of Greece, 2001)
The Mw=7.4 Izmit (Kocaeli) earthquake of August 17, 1999 (Turkey) ruptured 100 km at least surface faults on land along the northwestern branch of the North Anatolian Fault Zone (NAFZ). Although the preexisting structures of NAFZ has been divided into segments, showing stepover and pull apart geometry, the earthquake ruptures are generally linear, E-W striking (N80°-100°), right-lateral. In small scale and on the recent sediments they show very typical strike-slip displacements (2 to 5m), pop-ups and pressure ridges (N 40- 70°), Ρ (N80°), R (N100-1100) and R’ ( N350°) Riedel shears, extensional cracks (N115°-135°), restraining and releasing bends and small pull apart structures. In the epicentral area (Gölcük-Tepetarla) the seismic ruptures did not follow any known or previously mapped fault, but the morphology and the Digital Elevation Model (DEM) show typical and recognizable paleo-earthquake features. That is elongated valleys, shutter ridges, high angle slopes, scarplets, stream offset; while trenching tectonostratigraphy indicate palaeo sag-ponds (clayly deposits) and palaeo liquefaction (C14 dating-Holocene-historical deposits 200 to 11,000 yr. BP).